Memperluas Jaringan Access Point Internet - Rahman, Abdul; Mulyati, Mulyati; Inayulah, Inayatulah (Universitas Multi Data Palembang, Fakultas Ilmu Komputer dan Rekayasa, 2024)
The limited range of wireless access points presents a problem providing internet access in offices with vast and separate buildings. The Camat office in Semendawai Timur Subdistrict, East OKU Regency, features a building structure with multiple separate buildings, including a pavilion commonly used for various meetings. To overcome this challenge, the team conducted a community service initiative that offered training on expanding the existing access point network, enabling it to cover multiple areas within the Camat office. The initiative was warmly welcomed by the staff, who showed great enthusiasm for the access point network expansion training. As a result of this training, employees at the Camat office gained the knowledge and skills to configure wireless routers to extend the available access point network. This capability can also be applied in other locations, such as homes, health centers, and other places where network expansion is needed..